Factors measuring the readiness of teacher educators’ to use web 2.0 technologies - Saira Soomro; Arjumand Bano; Yonis Gulzar; Golooba Moses (Discover Sustainability)
Abstract Web 2.0 has opened many opportunities and avenues in education, especially in tertiary education. The open nature of Web 2.0 has enabled teachers and students to access, share, collaborate, and communicate knowledge around the world with just one click. Web 2.0 tools have been frequently used in teacher education in session planning and designing strategies for the teaching–learning process. Pakistan's public and private sector universities offer teacher education programs. Due to the significant influence of Web 2.0 technologies, there have been a rising number of studies on the use, effects, and perceptions of Web 2.0 technologies in education. However, there was a need for study in the Pakistani scenario, which could uncover teacher educators' practices regarding the use of Web 2.0. To better understand the factors that influence teacher educators’ decisions to adopt Web 2.0 technologies. This study used the Decomposed Theory of Planned Behavior (DTPB) framework aimed to unwind teacher educators' behaviors and practices for Web 2.0 technology usage. The research design of this study was exploratory with a quantitative approach. The data was collected through an adopted DTPB scale-based survey questionnaire that provided a snapshot of the behaviors, attitudes, opinions, and beliefs of teacher educators. The population of the study was comprised of teacher educators of the teacher education departments from public and private sector universities of Sindh province in Pakistan. From both sectors, a total of 156 subjects were targeted for data collection, out of which 73 participants responded. This research uses descriptive analysis and inferential analysis to establish the overall tendency of responses from individual teacher educators and to note how this tendency varies among both sectors. Based on the findings, the results depict how a large population views the usage of Web 2.0 technologies in the teaching–learning process and the diversity of both sectors.